Parole e gesti dell’insegnante nell’ora di italiano a stranieri (e non solo)La nozione di continuum contestuale: La nozione di continuum contestuale - Nobili, Claudio (Incontri. Rivista europea di studi italiani, 2022)
Teacher’s words and gestures in didactics of Italian to foreigners(and not only)The notion of contextual continuumThis paper starts from an extended concept of “plurilingualism” based on plurimodality in communication (i.e. the use of verbal and nonverbal codes in oral discourses). Assuming that plurilingualism and plurimodality are humans’ natural abilities to adapt verbal and nonverbal resources to the interaction, we propose a methodological approach to the study of teacher’s language and hand gestures in the Italian as a foreign language or L2 classroom (even if our conclusion is valid for the general classroom context). Before discussing the approach, in the first part of the paper we present a brief review of the literature on language and gestures for didactic activities in the contexts of Italian as L1/L2 (or as a foreign language). In the second part the approach called “contextual continuum” is introduced and exemplified. Our aim is to demonstrate that Italian (and not Italian) teacher’s language and gestures in the classroom context are relevant if compared with contexts which are progressively not the classroom. More specifically, in a laboratory context gestures appear significantly simplified and reduced.